Nieznany list Marii Komornickiej - Bourkane, Mateusz (My University, 2013)
The study presents an unpublished letter by Maria Komornicka, which the poet sent in July 1899 to her aunt, Aleksandra Oszacka. The epistolary communication, which contains several pieces of information about the life and activities of the poet living in Warsaw, can be a valuable material for researchers interested in her biography.
An Unknown Letter by Maria Komornicka
Keywords: Maria Komornicka; epistolography; Young Poland